2022
DOI: 10.3390/antiox11040720
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Industrial Potentials of Lemongrass Essential Oil as a Food Preservative: A Review

Abstract: The food industry is growing vastly, with an increasing number of food products and the demand of consumers to have safe and pathogen-free food with an extended shelf life for consumption. It is critical to have food safe from pathogenic bacteria, fungi, and unpleasant odors or tastes so that the food may not cause any health risks to consumers. Currently, the direction of food industry has been shifting from synthetically produced preservatives to natural preservatives to lower the unnecessary chemical burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“…Moreover, it was shown that powdered leaves of matcha green tea and moringa added to white chocolate during the tempering process improved its antioxidant capacity due to the high amounts of polyphenols in green tea [ 146 , 153 ]. Another recent study showed that lemongrass essential oil has a higher applicability as a food preservative due to its content in terpenes [ 154 ]. From natural marine algae, seaweeds are known to have several properties to act as natural preservatives extending the shelf life of perishable foods and at the same time not affecting their quality or causing side effects.…”
Section: Antioxidants As Food Additivesmentioning
confidence: 99%
“…Moreover, it was shown that powdered leaves of matcha green tea and moringa added to white chocolate during the tempering process improved its antioxidant capacity due to the high amounts of polyphenols in green tea [ 146 , 153 ]. Another recent study showed that lemongrass essential oil has a higher applicability as a food preservative due to its content in terpenes [ 154 ]. From natural marine algae, seaweeds are known to have several properties to act as natural preservatives extending the shelf life of perishable foods and at the same time not affecting their quality or causing side effects.…”
Section: Antioxidants As Food Additivesmentioning
confidence: 99%
“…Citral was reported as the major component in the lemongrass essential oil, with high amounts of geranial, neral, myrcene, limonene, cosmene, o-cimene, α-terpinolene, verbenol, citronellal, linalool, cis-carveol, nerol, atrimesol, carveol, geranyl acetate, and caryophyllene [ 93 ]. These compounds make this essential oil effective against L. monocytogenes , Yersinia , E. coli , Staphylococcus , S. Typhimurium , L. plantarum , P. aeruginosa , B. cereus , B. subtilis , Enterococcus faecalis , and Enterobacter aerogenes [ 93 ].…”
Section: Natural Antimicrobial Agents and Their Effect On Meat Productsmentioning
confidence: 99%
“…Although their antimicrobial activity is interesting and promising, the cytotoxicity of some essential oils could limit their use in foods [ 49 , 79 ]. For example, the excessive consumption of lemongrass essential oil may cause tumors, gene damage, and carcinogenic effects [ 93 ], while the cytotoxic activity of thyme essential oil was related to the presence of α -pinene, borneol, and β -caryophyllene [ 129 ]. Moreover, essential oils obtained from Salvia sclarea L., Cinnamomum camphora , Origanum compactum , Citrus aurantium Mentha piperita , and Eucalyptus globulus were investigated for their toxicological constituents [ 112 ].…”
Section: Natural Antimicrobial Agents and Their Effect On Meat Productsmentioning
confidence: 99%
“…In line with essential oils, novel vegetal sources have been proposed to increase food shelf-life, such as oil lemongrass essential oil, which contains relevant terpenes, responsible for antioxidant activity. However, their stability and volatility at high temperatures would suggest employing innovative technologies, including microencapsulation, nanoemulsion and edible films, to add them to foods [ 12 ]. On the other hand, other less studied sources of antioxidant compounds have been presented in this Special Issue.…”
Section: Novel Sources Of Natural Antioxidantsmentioning
confidence: 99%